Study the Possibility of Recycling Damaged Thermostone in Thermostone Najaf Plant - Razzaq Hasan, Ammar; Hussein Hamzah, Khaldoon (International Journal of Engineering and Technology, 2018)
Research include the possibility of benefiting from a damaged thermostone and output from several sources, including manufacturing and damaged operations during transportation and the user to measure the durability other from other sources as substitutes for Raw Materials involved in thermostone industry while maintaining the quality of the product and its properties and thus reducing the raw materials consumed in production processes where it was noted that the compensation of 15% of each of sand and cement. Thermostone mix give the results of the power of good bear while maintaining on its properties and that the compensation cement results were better than the compensation sand and therefore can benefit from a damaged Thermostone in recycling.Â Â